A revised prediction model for natural conception. Issue 6 (June 2017) - Bensdorp, Alexandra J.; van der Steeg, Jan Willem; Steures, Pieternel; Habbema, J. Dik F.; Hompes, Peter G.A.; Bossuyt, Patrick M.M.; van der Veen, Fulco; Mol, Ben W.J.; Eijkemans, Marinus J.C.; ,
Highlights: The Hunault model is the standard prediction model for natural conception. This model can be revised by including additional predictors. The revised model is applicable to a broader population. The revised model needs to be externally validated. Abstract: One of the aims in reproductive medicine is to differentiate between couples that have favourable chances of conceiving naturally and those that do not. Since the development of the prediction model of Hunault, characteristics of the subfertile population have changed. The objective of this analysis was to assess whether additional predictors can refine the Hunault model and extend its applicability. Consecutive subfertile couples with unexplained and mild male subfertility presenting in fertility clinics were asked to participate in a prospective cohort study. We constructed a multivariable prediction model with the predictors from the Hunault model and new potential predictors. The primary outcome, natural conception leading to an ongoing pregnancy, was observed in 1053 women of the 5184 included couples (20%). All predictors of the Hunault model were selected into the revised model plus an additional seven (woman's body mass index, cycle length, basal FSH levels, tubal status, history of previous pregnancies in the current relationship (ongoing pregnancies after natural conception, fertility treatment or miscarriages), semen volume, and semen morphology. Predictions from the revised model seem to concur better with observed pregnancy rates compared with the Hunault model; c-statistic of 0.71 (95% CI 0.69 to 0.73) compared with 0.59 (95% CI 0.57 to 0.61).